2010
DOI: 10.1007/s11136-010-9628-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the EORTC head and neck–specific quality of life questionnaire in disease-free Greek patients with cancer of pharynx and larynx

Abstract: The Greek version of EORTC H&N35 in conjunction with the EORTC C30 is a valid and informative tool in assessing quality of life in Greek patients with cancer of larynx and pharynx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Only Chaplin et al [80], Infante-Cossio et al [71], Borggreven et al [81], Nalbadian et al [82] and Huang et. al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Chaplin et al [80], Infante-Cossio et al [71], Borggreven et al [81], Nalbadian et al [82] and Huang et. al.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that the combination of surgery and radiotherapy led to more pain in patients when compared to patients treated with surgery or radiotherapy only [62,90]. Other studies described more pain among patients who were treated with chemoradiotherapy when compared to patients who had undergone other treatment methods [54,82]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in most of those studies, the questionnaires were administered after a follow-up period ranging from 40 months to 6 years. [14][15][16] Singer et al reported data from a German group of patients treated with SCL. 12 The questionnaires were administered after a longer follow-up period than that used in our study.…”
Section: Resultsmentioning
confidence: 99%
“…The head and neck specific questionnaire EORTC QLQ-H&N35 consists of seven multiple-item scales and six symptom items with a total of 35 questions that assess pain, swallowing, senses (taste and smell), speech, social eating, social contact, sexuality, teeth problems, trismus, dry mouth, sticky saliva, cough and feeling ill. A high score for a symptom scale indicates a higher level of symptoms or problems. This questionnaire has been used in several studies including Bjordal et al (26), Aplak et al (40), Boscolo-Rizzo et al (41), Nalbadian et al (42), and Baharvand et al (25). According to the results of this study, the mean score of QoL after being affected by radiationinduced gustatory disturbance was 20 points more than the mean score of QoL before radiation therapy, which is an indicative of a poorer QoL after being affected by radiationinduced gustatory disturbance.…”
Section: Discussionmentioning
confidence: 99%